2013
DOI: 10.1155/2013/181758
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of a New Series of N‐1,3‐Benzothiazol‐2‐ylbenzamides

Abstract: Enterococcus faecalisis a Gram-positive commensal inhabitant of the intestinal tract of humans, animals, and insects. However, it is also an opportunistic pathogen and has emerged as a leading cause of hospital-acquired extraintestinal infections. Fluoroquinolones have been frequently used to treatE. faecalisinfections, and the emergence of fluoroquinolone-resistantE. faecalisstrains has recently been reported in several countries. Thus, the identifications of new antibiotics specifically directed toE. faecali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Chemistry. Compounds 1a-l and 2b-e were previously reported by this group [18]. Compounds 1m,n and 2a were prepared as reported in Schemes 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemistry. Compounds 1a-l and 2b-e were previously reported by this group [18]. Compounds 1m,n and 2a were prepared as reported in Schemes 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been reported that antimicrobials often induce cytotoxicity via apoptotic mechanism, thus making themselves candidates as new tools for anticancer therapy. In the last decade, our research group was interested in the design, synthesis, and biological evaluation of novel benzothiazole derivatives as antimicrobial agents [8,10,18]. Thus, to further investigate the panel of activity for this class of compounds, we decided to study some of them as potential anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years the considerable attention is focused on practical application in the agriculture of different classes of low molecular weight heterocyclic compounds, derivatives of pyrimidine, pyrazole, isoflavones, pyridine, oxazole, oxazolopyrimidine as effective substitutes of traditional plant growth regulators, herbicides, fungicides and antimicrobial agents [14][15][16][17][18][19][20][21][22][23][24][25][26] . Testing of different classes of chemical low molecular weight heterocyclic compounds on human and animal cells indicated their activity against cancer, viral, bacterial, fungal, infectious, inflammatory and nervous diseases [27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…We recently studied two different series of 1,3‐benzothiazoles both as antifungals against Candida spp . and antibacterials, in particular against Enterococcus faecalis . In the last year, we determined for the first time the X‐ray crystallographic structure of E .…”
Section: Introductionmentioning
confidence: 99%